Seeking sustainable development: Community profiling using the UN's sustainable development goals - Penullar, Neil Oliver T. (Animo Repository, 2016)
With the adoption of the UN Sustainable Development Goals in 2015, nations now have a development framework that seeks to eradicate poverty, realize human rights and heal the environment at the same time. Without effectively localizing the SDGs however, realizing these goals may be difficult and slow. The purpose of this study is to gather SDG-related baseline information for Brgy. 707, Manila. Data from the Community-Based Monitoring System (CBMS) Census conducted for all 226 households in the community were used to identify SDG gaps and possible programs that DLSU may initiate to help the community. Low high school participation rate, limited internet access, income inequality, PWD and solo parent exclusion, limited recycling activities and unavailability of disaster survival kits are some of the concerns identified. Revisions in the CBMS framework, software and instruments must be done to integrate SDG indicators and targets not included in the CBMS.